THE EFFECT OF PRODUCT QUALITY, PRICE PERCEPTIONS, AND PROMOTIONS ON PURCHASING DECISIONS MEDIATION OF BRAND IMAGE - Lawasa, Abdul Mutakhir; Adam, Rosida P; Rombe, Elimawaty (JURNAL INTERNASIONAL UNIVERSITAS TADULAKO, 2023)
This research was conducted with the aim of understanding and analyzing the influence of product quality, price perception, promotion on purchasing decisions and brand image as mediating variables on iPhone consumers in Palu City. Explanatory research is used to find out the relationship between variables. The population size is not yet known with certainty so the sample was taken using a purposive sampling technique based on certain considerations and using the Roscoe method (number of variables multiplied by 20) so that the total research sample was 100 people. Data analysis uses descriptive statistics and SEM techniques through path analysis using Smart PLS. The research results show that (1) product quality has a significant effect on brand image, (2) Price perception has a significant effect on brand image, (3) Promotion has a significant effect on brand image, (4) Product quality has a significant effect on purchasing decisions, (5) Price perception has no significant effect on purchasing decisions, (6) Promotion has a significant effect on purchasing decisions, (7) Brand image has a significant effect on purchasing decisions, (8) Product quality has no significant effect on purchasing decisions through brand image (9) Price perception has an effect not significant on purchasing decisions through brand image (10) Promotion has no significant effect on purchasing decisions through brand image.